Developing Interactive Arabic Teaching Materials Based on Heyzine Flipbook for Junior High School Students - 'Aini, Putri Nur; Faiqoh, Putri Kholida; Sholihuddin, Ahmad (Proceeding International Conference on Education, 2025)
This research was conducted in response to the limited availability of effective and engaging Arabic language teaching materials at MTs. Raudlatut Thalabah. The existing instructional resources primarily consisted of student worksheets (LKS), with minimal use of multimedia tools, leading to low student engagement and difficulty in understanding the material, particularly the topic of at-ta’aruf. The purpose of this research was to develop Arabic teaching materials using Heyzine Flipbook and to evaluate their strengths and weaknesses. The research employed a Research and Development (R&D) approach using the ADDIE instructional design model, which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. Data collection methods involved observation, interviews, documentation, questionnaires, and tests. The final product was an interactive flipbook enriched with audio, video, and quizzes. Validation results indicated that the material was highly valid in terms of content (90.5%) and media (82.7%). Feedback from teachers and students was also very positive, with response rates of 85.6% and 89.2%, respectively. Additionally, the effectiveness of the material was demonstrated by an normalized gain (N-gain) score of 76.5%, categorized as effective. The advantages of the developed material include its digital format, online accessibility, multimedia support, and interactive quizzes with automatic scoring. However, limitations remain, such as the material’s focus on a single topic (at-ta’aruf) and its reliance on an internet connection, which restricts offline accessibility.